Providing baseline data for conservation–Heart rate monitoring in captive scimitar-horned oryx - Leimgruber, Peter; Songsasen, Nucharin; Stabach, Jared A.; Horning, Megan; Reed, Dolores; Buk, Tara; Harwood, Arielle; Layman, Lawrence; Mathews, Christopher; Vance, Morgan; Marinari, Paul; Helmick, Kelly E.; et al. (Frontiers in Physiology, 2023)
Heart rate biologging has been successfully used in wildlife to study changes in metabolic rates, responses to natural or human-caused stressors (e.g., hunting, landscape of fear), stress, and animal welfare. Yet, applications of heart rate monitoring to inform wildlife management and conservation, especially for threatened and endangered species, are still rare. We successfully deployed subcutaneous heart rate monitors in eight captive scimitar-horned oryx, a species extinct in the wild, to assess their potential usefulness for monitoring the species during reintroduction activities. Detection accuracy was high for six of the individuals, ranging from 83 to 99%. We excluded data from two individuals with a right lateral placement of the biologger because accuracies were below 60%. Average heart rate across all six scimitar-horned oryx was 60.3 ± 12.7 bpm, and varied by about 12 bpm between individuals, with a minimum of 31 and a maximum of 188 bpm. Long-term patterns in heart rate were most strongly influenced by activity, and modulated by hour, season, and temperature. Circadian rhythms closely tracked activity with values increasing during the day and peaking near dusk. Seasonal heart rate patterns were reversed compared to activity. During winter, oryx were less active but exhibited higher relative heart rates, likely due to a combination of thermal stress from low temperatures and psychological stress from confined conditions in captivity. Patterns in activity for captive oryx were different from observations in the wild, where the species shows strong seasonal shifts from diurnal activity in the cool season to predominantly nocturnal activity in the hot dry season. We expect a similar pattern in heart rate in wild scimitar-horned oryx because of reduced overall activity and metabolic rate during the hot dry season, when food is scarce and evaporative water loss is high. When linked with movement data, the use of heart rate monitors in reintroduced scimitar-horned oryx would allow managers to assess how released animals adapt to their new environment and advance our knowledge about behavioral and physiological adaptations of desert ungulates to their extreme environment.